(untitled) (Journal of actual problems of jurisprudence, 2018)
Issues of implementation of the principles of criminal procedure are actualized in connection with the execution of political – legal state program aimed at enhancing the rule of law, the fight against crime. All these indicators become apparent that the principles of due process require further study in the theory of criminal – procedural science, which must also rest on the achievements of the constitutional and sectoral rights, domestic theory of law. Key words: principles of due process, the implementation of the principles of criminal procedure, protection of the rights and freedoms of the individual, inviolability of the person, the detention of the suspect.